Assessment of Tsunami Potential in Bali Using TOAST Modeling: Implications for Disaster Risk Reduction - Ni Putu Yuni Nurmalasari; I Gusti Agung Putra Adnyana (Kappa Journal, 2026)
This study aims to evaluate the tsunami hazard potential in the Bali region using multi-scenario numerical modeling to support disaster mitigation and early warning planning. Tsunami simulations were performed using the Tsunami Observation and Simulation Terminal (TOAST) with the EasyWave module. The model inputs were derived from the BMKG historical earthquake catalog and the 2017 Indonesian Seismic Hazard Map (PUSGEN), focusing on the Flores Back Arc Thrust segment north of Bali. Four earthquake magnitude scenarios (Mw 7.0, 7.2, 7.5, and 8.5) were simulated to estimate maximum wave heights and tsunami arrival times along the Bali coastline. The results indicate that nearly all coastal areas of Bali are vulnerable to tsunami impacts. In the worst-case scenario (Mw 8.5), maximum wave heights exceed 5 m in Sanur (Denpasar), Klungkung, and southern Karangasem, with short arrival times ranging from 5 to 22 minutes, corresponding to the highest warning level. Although moderate-magnitude scenarios (Mw 7.0–7.5) generate lower wave heights, tsunami arrival times remain rapid, indicating limited evacuation opportunities. These findings highlight the urgency of multi-scenario tsunami hazard assessment, enhancement of tsunami early warning systems, and improvement of evacuation preparedness to reduce tsunami risk in Bali.